PERANAN ORANG TUA DALAM MELATIH BICARA ANAK TUNARUNGU DI SLB WACANA ASIH PADANG - Rilla Kurniawan (Universitas Negeri Padang, 2015)
Abstract—–The students with hearing impairment had obstacles to acquire language. Therefore, the roles of parents are highly expected to develop their speaking ability. The task should not be solely assigned to the teachers. The purpose of this research was to figure out the efforts done by the parents to help the students with hearing impairment to develop their speaking ability, the obstacles encountered by the parents, and the efforts done to overcome the obstacles. This was a descriptive research, the population was the parents of students with hearing impairment at SLB WacanaAsih Padang whose children registered in Academic Year 2014. All of the population was taken as the sample. The data was gathered through questionnaire and analyzed by using descriptive analysis technique and was presented in percentage. The results indicated that the efforts to develop the students with hearing impairment ability to speak at SLB WacanaAsih had been fairly good. Before registering their children to SLB, the parents had consulted their problem to ENT doctors. The students’ speaking ability was developed by exposing the students to things or objects found in their daily life with patiently and affectionately. Few of parents got hearing aids for their children. Unfortunately, the results achieved were not optimal yet. The difficulties found by the parents were the children relatively had short attention span and were easily got bored. The drilling was done continuously in a short time. The drill to develop the students’ speaking ability was conducted by using media such as toys, cakes eaten by the children and so on. To find the appropriate was to develop their speaking ability, the parents shared information one to another and sometime they consulted them to the teachers. Keyword —- The Roles of Parents in Developing the Speaking Ability of the Students with Hearing Impairment